Preparation of heterostructured WO3/TiO2 catalysts from wood fibers and its versatile photodegradation abilities - Likun Gao (Nature Portfolio, 2017)
Abstract A facile route was adopted to synthesize heterostructured WO3/TiO2 photocatalysts from wood fibers through a two-steps hydrothermal method and a calcination process. The prepared WO3/TiO2-wood fibers were used as photocatalysts under UV irradiation for photodegradation of rhodamine B, methylene blue and methyl orange. In calcination process, the wood fibers acted as carbon substrates to prepare the WO3/TiO2 photocatalysts with high surface area and unique morphology. Thus, the significant enhanced photodegradation efficiency of the organic pollutants with the WO3/TiO2-wood fibers under UV irradiation was obtained. The photodegradation rates are measured which confirms the highest performance of the WO3/TiO2-wood fibers after calcination in comparison to the TiO2-wood fibers after calcination and the pure WO3/TiO2 after calcination. Moreover, the photodegradation efficiency of the WO3/TiO2-wood fibers after calcination under visible light is high. Our results demonstrated that the WO3/TiO2-wood fibers after calcination are a promising candidate for wastewater treatment in practical application.